Numerical analysis of stress concentration factors on tensile armour wires inside the end-fitting of an axially tensed unbonded flexible pipe - Anastasiadis, Panagiotis S.; Theotokoglou, Efstathios E.; Michailides, Constantine (My University, 2020)
The present paper examines the case of a metal based unbonded flexible pipe under a number of axial tensile operational loads of varying intensity, expressly focusing on the response of the segments of the pipe’s tensile armour wires that lie inside the pipe’s End-Fitting (EF), with intent to track the development of high stress concentration areas there and assess the stress concentration factors (SCF) involved. Additionally, a parametric study is performed, to identify potential factors that might affect the maximum SCF values measured on these wire segments inside the EF. Based on the parametric study’s findings, an approximate relationship for evaluating the expected maximum SCF on the tensile wire inside the EF is developed. The paper adopts a numerical approach to the problem, based on the development of a two-dimensional finite element model for evaluating the wire’s response to axial tensile operational loads. The model considers both the effects the EF’s assembling procedure and the Factory Acceptance Test (FAT) have on the behavior of wire segments lying inside the EF. An analytical approach is employed as a benchmarking tool of the numerical model’s performance.
Keywords: Axial tensile loads; End fitting; Finite elements; Stress concentration factor; Tensile armour wire; Unbonded flexible pipe